Addendum to "Marx's analysis of ground-rent: Theory, examples and applications" - Deepankar Basu (University of Massachusetts, Department of Economics, 2018)
In this note, I offer a simple way to think about the determination of equilibrium levels of price and output for the agricultural commodity that makes explicit two important dimensions: (a) the role of aggregate demand for the agricultural commodity, and (b) profit maximizing behaviour of the capitalist farmers.
Keywords: 330